Sprawozdanie z działalności naukowej Wojewódzkiej i Miejskiej Biblioteki Publicznejim. Cypriana Norwida w Zielonej Górze za 2023 rok = Report on the Scientific Activity of The Cyprian Norwid Regional and City Public Library in Zielona Góra for 2023 - Bartkowiak, Przemysław (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The report on the scientific activity of The Cyprian Norwid Regional and City Public Library in Zielona Góra for 2023 presents various initiatives supporting the library's continuous academic development, including efforts related to the Zielona Góra Digital Library, publishing activities, organization of academic, popular science, and thematic conferences (trainings), as well as the organization of library science lectures, the Lubusz Laurel Awards, author meetings, and exhibitions. Additionally, the report highlights the ongoing professional development of Library?s staff in Zielona Góra, showcasing their achievements in areas such as academic and popular science publications and their active and passive participation in academic, popular science, and library science conferences and meetings. All activities presented in the report demonstrate the continuous scientific advancement of the Cyprian Norwid Regional and City Public Library in Zielona Góra.
Keywords: Wojewódzka i Miejska Biblioteka Publiczna im. Cypriana Norwida w Zielonej Górze; nauka; rozwój; sprawozdawczość; The Cyprian Norwid Regional and City Public Library in Zielona Góra; science; development; reporting